When We Collide : Sex, Social Risk, and Jewish Ethics - Epstein-Levi, Rebecca J. (Book collections on Project MUSE., 2023)
"When We Collide is a landmark reassessment of the significance of sex in contemporary Jewish ethics. Rebecca Epstein-Levi offers a fresh and vital exploration of sexual ethics and virtue ethics in conversation with rabbinic texts and feminist and queer theory. Epstein-Levi explores how sex is not a special or particular form of social interaction but one that is entangled with all other forms of social interaction. The activities of sex-doing it, talking about it, thinking about it, regulating it-are sites of ongoing moral formation on individual, interpersonal, and communal levels. When We Collide explores the development of Jewish sexual ethics, and represents an opportunity to move beyond the usual heteronormative accounts that are presented as though they were neutral representations of what "Judaism teaches about sex.""--